Change in obsessive beliefs as predictor and mediator of symptom change during treatment of obsessive-compulsive disorder – a process-outcome study. Issue 1 (December 2016) - Diedrich, Alice; Sckopke, Philipp; Schwartz, Caroline; Schlegl, Sandra; Osen, Bernhard; Stierle, Christian; Voderholzer, Ulrich
Abstract Background Cognitive models of obsessive-compulsive disorder suggest that changes in obsessive beliefs are a key mechanism of treatments for obsessive-compulsive disorder. Thus, in the present process-outcome study, we tested whether changes in obsessive beliefs during a primarily cognitive behavioral inpatient treatment predicted treatment outcome and whether these changes mediated symptom changes over the course of treatment. Methods Seventy-one consecutively admitted inpatients with obsessive-compulsive disorder were assessed with the Yale-Brown Obsessive-Compulsive Scale and the Obsessive Beliefs Questionnaire at treatment intake, after six weeks of treatment and at discharge, and with the Beck-Depression-Inventory-II at intake and discharge. Results Changes in obsessive beliefs during the first six weeks of treatment predicted obsessive-compulsive symptoms at discharge when controlling for obsessive-compulsive and depressive symptoms at intake in a hierarchical regression analysis. Multilevel mediation analyses showed that reductions in obsessive beliefs partially mediated improvements in obsessive-compulsive symptoms over time. Conclusions Our findings indicate that decreasing obsessive beliefs in inpatient cognitive behavioral therapy for obsessive-compulsive disorder might be a promising treatment approach.